Factors Associated with Shelter Dog Euthanasia versus Live Release by Adoption or Transfer in the United States - Cain, Cassie J. (Animals (Basel), 2021)
SIMPLE SUMMARY: United States animal shelters care for unwanted dogs until they are adopted, transferred to another facility, or euthanized. Previous studies have determined that certain phenotypic characteristics can be used to predict the outcome of shelter dogs. However, these earlier studies have typically been limited by sample size, shelter geographic location, and/or the number of shelters participating in the study, thus reducing generalized applicability of the results. The aim of this study was to test if certain characteristics of dogs in shelters predict the decision for those dogs to be euthanized rather than experience a live release by adoption or transfer. This study may be valuable to shelter staff because utilizing such phenotypic information can help shelter employees focus adoptability protocols, such as socialization and training programs, on dogs with a greater chance of being euthanized. ABSTRACT: The objective of this study was to identify phenotypic characteristics predicting the outcome of euthanasia for dogs entering shelters compared to live release. Individual dog records for 2017 were requested from shelters in five states (Mississippi, Pennsylvania, Michigan, Colorado, and Oklahoma) receiving municipal funding and using electronic records. Duplicate dogs were removed and records from 17 shelters were merged into a dataset of 25,047 unique dogs with variables of breed, gender, coat color, size, age, region, and time in shelter. Only data from dogs with the potential to be adopted (n = 19,514) were analyzed. From these data, a simple random sample of 6200 dogs was used for modelling. Variables describing coat length, estimated adult size, and skull type were imputed from the breed description. A Cox proportional hazard model with a random effect of shelter was developed for the outcome of euthanasia using manual forward variable selection and significance for variable retention at alpha = 0.05. A size by geographic region interaction was associated with the hazard of euthanasia (p = 0.0204). Additionally, age group and skull type were both associated with euthanasia compared to live release (p < 0.0001). The results of this study indicate that phenotypic characteristics of dogs are predictive of their hazard for euthanasia in shelters.